Can the French be happy, or can happiness be French? Contemporary French discourses on happiness as cultural value. Issue 3 (January 2016) - Willging, Jennifer
Abstract : In this essay I analyze recent French discourses about contemporary conceptions of "happiness, " in particular several recent books that critique the apparent ascension of happiness as a primary social value in contemporary France, replacing, according to their authors, older principles such as piety, honor, glory, or sacrifice. These writers explore the effects on the human psyche of the post-1968 dismantling of sexual, gender, class, geographical, and other boundaries, and they do not like what they see. They lament the ever-widening spaces in which human desire is allowed, indeed – they argue – compelled to roam in contemporary French society and warn of the dangers to which the increasing loss of limits, interdictions, and impossibilities exposes us all. Henri Lefebvre, spiritual father of May '68, argued that we are more likely to achieve happiness and fulfillment, at least sporadically, when we are experiencing "everyday life" (despite the increasing degree to which it was being organized and programmed by external forces), than when we are engaged in the "specialized activities" we have traditionally taken more seriously, such as work, study, worship, or politics. I argue that it is in part with this valorization of an "everyday" and thus "banal" happiness over more noble and rarefied states, such as joy, ecstasy, or rapture, and with its dubious transatlantic origins, that the authors of many of these critiques take issue.